Pertanggungjawaban Pidana Pelaku Tindak Pidana Penipuan Belanja Daring Dalam Metode Pembayaran Ditempat - Farhani, Muhammad Thufail; Isnawati, Muridah (Academos, 2023)
As a result of the development of information technology, there is a new form of fraud that is associated with the "criminal act of online fraud". Customer likes the convenience of on-site payment options because it frees them from the burden of admin fees and is easier to process payments. Cash on delivery options have a high level of risk, contributing significantly to the prevalence of eIectronic transaction fraud. Sellers use a variety of strategies in the hope of increasing their revenue, most of which will ultimately be unavailable to the person who buys the goods sold by the seller. This research uses normative legal research using the statutory approach method. The criminal liability of online shopping fraud in the cash on delivery method can be charged to Paragraph 45A section (1) of the ITE Law